An Example from the Phonology-Phonetics Interface: Rhotics - Göktuğ BÖRTLÜ (Dilbilim Araştırmaları Dergisi)
Although the class of rhotics is not arbitrary regarding its phonological behavior thanks to its synchronic and diachronic stability and sonorant characteristic in syllable structures, it is arbitrary in terms of phonetic realizations. In a theory which allows such arbitrary phonetic realizations, there should be a phonology-phonetics interface which converts phonological primes into phonetic objects. The post-phonological spell-out, the interface between modular phonology and phonetics which have distinct vocabularies, acts as a dictionary, helping abstract phonological objects surface as certain phonetic articulations. As exemplified by rhotics in this study, phonetic qualities do not seem to be sufficient in defining the phonological identity of a segment. According to the language-specific post-phonological spell-out, it is possible for some rhotics to be realized as [r], some as [ʀ] and others as [ʃ] and all of these are assumed to be completely arbitrary. This assumption is also in line with substance-free phonology which argues that phonological objects do not have any phonetic substance associated with them.